Sugar-responsive transcription factor bZIP3 affects leaf shape in Arabidopsis plants - Sanagi, Miho (Plant Biotechnol (Tokyo), 2018)
Sugars are essential for plant metabolism, growth and development. Plants must therefore manage their growth and developmental processes in response to sugar availability. Sugar signaling pathways constitute a complicated molecular network and are associated with global transcriptional regulation. However, the molecular mechanisms underlying sugar signaling remain largely unclear. This study reports that the protein basic-region leucine zipper 3 (bZIP3) is a novel sugar-responsive transcription factor in Arabidopsis plants. The expression of bZIP3 was rapidly repressed by sugar. Genetic analysis indicated that bZIP3 expression was modulated by the SNF1-RELATED KINASE 1 (SnRK1) pathway. Moreover, transgenic plants overexpressing bZIP3 and dominant repressor form bZIP3-SRDX showed aberrant shaped cotyledons with hyponastic bending. These findings suggest that bZIP3 plays a role in plant responses to sugars and is also associated with leaf development.